Pengaruh Harga, Citra Merek, Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Provider Tri (3): (Studi Kasus pada Mahasiswa Manajemen Angkatan 2020 di Universitas Bhayangkara Jakarta Raya Bekasi) - Damar Asmarani; Wirawan Widjanarko; Franciscus Dwikotjo Sri Sumantyo (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This study aims to test the influence of Price, Brand Image and Service Quality (independent variables) on Purchasing Decisions (dependent variables). This type of research is quantitative using a questionnaire via Google Form. Sampling using the purpose sampling method so that the number of samples is set at 100 respondents. The analysis technique used in this study uses SPSS version 25. The results of this study explain that, in management students of the 2020 intake at the University of Bhayangkara Jakarta Raya Bekasi, the variables of price, brand image, and service quality have a positive effect on purchasing decisions for the Tri (3) provider. The study has object limitations on management students of the 2020 intake at the University of Bhayangkara Jakarta Raya Bekasi and combines the variables of price, brand image, and service quality on purchasing decisions for the Tri (3) provider.